DAYA TERIMA DAN ZAT GIZI PANCAKE SUBSTITUSI KACANG MERAH (PHASEOLUS VULGARIS L) DAN DAUN KELOR (MORINGA OLEIFERA) SEBAGAI ALTERNATIF JAJANAN ANAK SEKOLAH[Acceptability and Nutrient Content of pancake Substituted with Red Bean (Phaseolus vulgaris L) and Moringa Leaves (Moringa oleifera) as an Alternative Snack for School Aged Children] - Heluq, Dinda Zhara; Mundiastuti, Luki (Media Gizi Indonesia, 2018)
Nutritional problems among school aged children are still found in Indonesia. This problems caused by poor eating habit, such as the low consumption of vegetables and high consumption of snacks which only contain the high energy, fat, and sugar yet low in protein and micro nutrients. Improving the quality of snacks can be conducted to overcome the nutrition problems. This research was aimed to analyze the effect of substitution of red beans and moringa leaves to the acceptance and nutrient content (protein and calcium) in pancakes. This was an experimental study with the Completely Randomized Design. Five with repetitions with three formulas, i.e., a control formula and two modifi cation formulas (substituted with red beans and moringa leaves). The untrained panelist were 30 students of the fi fth-grade elementary school. Data was analyzed by Friedman and Wilcoxon Sign Rank (α=0.05) tests. The acceptance level demonstrated that the F1 was the most preferred formula by the panelists. There were no signifi cant differences in the aroma, fl avour, and texture (p>0.05) between formulas. Nonetheless, there was a signifi cant difference in color (p<0.05) between F0 and F1. The laboratory test showed that the protein and calcium content per 100 g of the F1 were, 5.27 g (7% higher than the F0) and 254,8 mg (304% higher than the F0) respectively. The F1 was the chosen formula because it had better acceptability and nutrient content than the control formula. The best acceptance, but also had. Thus, it is potential to become an alternative snack for school aged children.